ZIRCONS FROM ULTRAMAFIC-MAFIC INTRUSIONS AT NORIL'SK AREA (RUSSIA): A COMPOSITIONAL AND U-PB STUDY - Malich K.N.; Petrov O.V.; Badanina I.Yu.; Presnyakov S.L. (My University, 2007)
World-class platinum-group-element (PGE)-Cu-Ni deposits closely linked to intracontinental paleorift-related ultramafic-mafic intrusions are located in the northwestern corner of the Siberian craton, Russia. In spite of its significant metallogenic potential, age constraints for majority of the ore-bearing intrusions are poorly defined. Similarly, timing and duration of the ore concentration responsible to form an economic deposit has been rarely evaluated quantitatively.